¿Por qué cambió la legislación aduanera en el Perú? - La Noire Núñez, José Antonio (2021)
Through this article, the author intends to inform the reader about the customs reform which took place in Peru between 2015 and 2020. Such reform, on one hand meant an improvement in our national legislation as the Customs Administration regulated more efficiently the foreign commerce operators and; on the other hand, implied a modernization in the customs service, applying quality and security systems that allow managing customs clearances in a more agile and simplified way, also ensuring full traceability of cargo and reducing final costs.